NCLEX-RN review : complete video course (Pearson IT certification., 2015)
"The NCLEX-RN review complete video course provides more than 11 hours of concise coverage of all the topics a candidate needs to study for the registered nurse licensing exam. It blends the ideal level of discussion, drawings, tables, and case studies into an easily digestible format for study. The authors give students tips for passing the exam from using memory devices to understanding question structure to practice with alternative item style questions. This Complete Video course also includes interactive hands-on exercises available on the course's streaming site to help you further study for the exam. Section quizzes, glossary quizzes, and a practice final exam are also presented through the course's interactive site, so you have all the material needed to prepare for the exam."--Resource description page.